2022
DOI: 10.1590/fst.50921
|View full text |Cite
|
Sign up to set email alerts
|

Changes in structural and chemical composition of insoluble dietary fibers bound phenolic complexes from grape pomace by alkaline hydrolysis treatment

Abstract: This study was aimed at explanation of evolution process of bound phenolics from IDF through structural modifications after alkaline hydrolysis along with free phenolics and functional characteristics. SEM results depicted that IDF with bound phenolics exhibited denser, more compact and tubular shape whereas, the surface features of alkali-hydrolyzed residue exhibited clear fragmentation, wrinkling and porosity on outside surfaces. Microstructure changes due to alkaline hydrolysis caused disintegration of link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Te results of the present study for calories content of whole wheat four and moringa leaf powder have been in close afrmation with the earlier studies, wherein the contents of the calories for whole wheat four and moringa leaf powder were seen in a similar range, i.e., 11.25% and 26.28%, [40,43]. In a report by Jiang et al [45], ginseng insoluble dietary fber (GSI) was added to the wheat bread. and up to the addition levels of GSI, the fortifed bread showed improvement in mineral, proteins, and fber contents as compared to that of control.…”
Section: Proximate Composition Of Mlp-supplemented Leavenedsupporting
confidence: 89%
“…Te results of the present study for calories content of whole wheat four and moringa leaf powder have been in close afrmation with the earlier studies, wherein the contents of the calories for whole wheat four and moringa leaf powder were seen in a similar range, i.e., 11.25% and 26.28%, [40,43]. In a report by Jiang et al [45], ginseng insoluble dietary fber (GSI) was added to the wheat bread. and up to the addition levels of GSI, the fortifed bread showed improvement in mineral, proteins, and fber contents as compared to that of control.…”
Section: Proximate Composition Of Mlp-supplemented Leavenedsupporting
confidence: 89%
“…Additionally, a peak at 1510 cm –1 in corncob samples is attributed to the C–C stretch inside aromatic rings, which are present in phenolic acids and lignin . Corncob and nopal samples showed peaks at 1632 and 1621 cm –1 , respectively, associated with the adsorbed water . The woody ring samples exhibited a higher signal and variations in the position of peaks in the alkyl region, which ranged from 2800 to 3000 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…44 Corncob and nopal samples showed peaks at 1632 and 1621 cm −1 , respectively, associated with the adsorbed water. 48 The woody ring samples exhibited a higher signal and variations in the position of peaks in the alkyl region, which ranged from 2800 to 3000 cm −1 . These differences can be attributed to the symmetry of alkyl groups.…”
Section: Acs Foodmentioning
confidence: 95%
“…Studies have shown that the signal peaks about 14–15°and 21–23.5° could be due to the presence of cellulose crystals. Furthermore, the presence of non-crystalline cellulose, hemicellulose and lignin is reported to cause amorphousness in DFs ( Jiang, Wu, Ramachandra, Zhao, & Ameer, 2021 ). With regards to AL-DF, front peaks were observed at 2θ angles of 32.56, 36.87° and 43.29°, whereas these peaks were not observed in case of W-DF and WB-DF.…”
Section: Resultsmentioning
confidence: 99%